Sudan Crisis: In-depth Gender Assessment Report - United Nations Women (United Nations, 2024)
This Gender Assessment aims to provide an in-depth gender analysis. It provides data that is sex and age disaggregated to understand the gender-differentiated needs, priorities, coping strategies, risks, insecurities, and vulnerabilities of the conflict, considering different gender roles and responsibilities as well as the intersectionality factors to inform an equitable and effective humanitarian response and give recommendations for gender-sensitive humanitarian programmes, that promote justice and equality to women, men, girls, and boys of all, ages, statuses and vulnerabilities.